Sikeres vállalatok – sikeres település: Szentgotthárd - Palkovits, István (Tér és Társadalom, 1997)
The West Hungarian region was a winner of the transition period as result of its advanced geographical situation. Szentgotthárd, a small town of 9015 inhabitants is part of this area as the centre of a small region in the vicinity of the Hungarian-Austrian border. Local industries evolved in the 19 th century and the economic prosperity resulted in an expansion and differentiation of local services (public administration, education, and cultural institutions). The favourable economic and social trends were hindered by the modification of the national border (1920) and latter by the foreign policy of the communist era. In the transition period, local factors of economic prosperity such as cross-border co-operation and traditional regional functions revived. The basis of rapid economic changes was foreign investments in the local industries (textile, machinery, and metallurgy) that were attracted by infrastructure facilities and skilled labour. Furthermore, shopping tours of Austrian citizens also had favourable effect on local services and trading. The prosperity involved advantageous changes in demographic trends (particularly, in terms of skill and age). Despite the rapid growth in local economy, the future of Szentgotthárd is full of question marks. Decisions made on the local industry are made in distant cities with rno regard to the interests of people living in the region. Local enterprises should be strengthened to stabilise economic development and make it less dependent on outer resources in long term. Furthermore, there is a need for better communication between local people, local authorities and the enterprises to enhance local cultural facilities and improve the quality of natural and built environment. Perspectives of local education and social organisations are also significant parts of long-term development that should be unravelled.